Legal and administrative remedies in environmental law in Nigeria: reform proposition (2013)
The article examines remedies in environmental law cases in Nigeria, in the light of problems faced by aggrieved litigants. It posits that despite the fact that there is a plethora of remedies and reliefs which a party can obtain as a result of a successful law suit, the impact of such available remedies are not adequate. The article examines remedies under the constitution, statutes and common law. The article states that Environmental litigation is a common vehicle for driving these remedies in order to transform the remedies into reliefs. Environmental litigation can take various forms which include civil actions based on tort, contract or property law, criminal prosecutions, public interest litigation or enforcement of fundamental human rights. The paper identifies reliefs within the enforcement powers of the courts which may include injunctive relief, restitution and remediation orders, continuous mandamus, damages, cost and fees, and criminal penalties. The paper also examines administrative remedies like direct government intervention, international intervention, environmental impact assessment and licensing. In addition, the article posits that other legal and administrative avenues need to be explored for optimal impact towards environmental sustainability and adequacy of remedies under the Nigerian legal system. At the legal angle, the article recommends that the principles of access to justice under Principle 10 of Rio Declaration should be incorporated into environmental law in Nigeria. It also recommends that rules on locus standi, limitation of action and pre-action notice should be relaxed in environmental cases. Administrative recommendations made in the article include establishment of a specialized environmental court, greater use of alternative dispute resolution methods, provision of effective supplementary complaint systems and the Use of Supplemental Environmental Projects.